1998
DOI: 10.1016/s0886-3350(98)80235-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative complications of 1000 phacoemulsification procedures: A prospective study

Abstract: The frequency of major and minor complications fell sharply after the first 150 operations and was maintained. This study may provide a guide for beginning phacoemulsification surgeons and a basis for experienced surgeons to compare their performance outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
2
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 12 publications
7
47
2
3
Order By: Relevance
“…70 This anterior capsular tear rate of 4% compares with other studies of conventional cataract surgery, which have demonstrated rates of 3.8% and 4.7-5.3%. 72,73 This study of FLACS also gave an overall incidence of 3.5% for PCR and 2% for posterior lens dislocation, although there was a trend towards fewer complications with time, and fewer complications among surgeons with previous experience with femtosecond lasers. 70 These figures may seem high when compared with those commonly quoted for conventional phacoemulsification.…”
mentioning
confidence: 76%
“…70 This anterior capsular tear rate of 4% compares with other studies of conventional cataract surgery, which have demonstrated rates of 3.8% and 4.7-5.3%. 72,73 This study of FLACS also gave an overall incidence of 3.5% for PCR and 2% for posterior lens dislocation, although there was a trend towards fewer complications with time, and fewer complications among surgeons with previous experience with femtosecond lasers. 70 These figures may seem high when compared with those commonly quoted for conventional phacoemulsification.…”
mentioning
confidence: 76%
“…[20][21][22][23][24][25][26][27][28][29][30][31] A variety of other curves were used to describe the learning relationship: logarithmic, [32][33][34][35] 43 In addition to the 24 papers using least squares regression, Monte Carlo simulation was used in another paper to estimate the shape of the learning curve. 44 The correlation between experience and outcome was tested by Spearman's correlation coefficient, 45,46 chi-squared test for trend, 47,48 or a Komolgorov-Smirnoff test. 49 In three studies an attempt was made to model the relationship between experience and outcome using repeated measures ANOVA.…”
Section: Univariate Trendmentioning
confidence: 99%
“…Up until the past few years, surgery was performed using either retrobulbar or peribulbar blocks. 8 In this study, all patients were operated using ATA, with the option of changing to assisted local anaesthesia (ALA) if necessary, utilising a retrobulbar or peribulbar block. 9 We also sought to assess patient recall of intraoperative anxiety, fear, and sensory perceptions, both visual and auditory, during second eye cataract surgery using ATA in comparison with their first eye surgery.…”
Section: Introductionmentioning
confidence: 99%